2017
DOI: 10.1021/acs.cgd.7b01443
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Anticancer Potential by Modifying the Structural Properties of a Family of Zinc Metal–Organic Chains Based on 4-Nitro-1H-pyrazole

Abstract: We have synthesized a novel family of metal−organic chains based on 4-nitro-1H-pyrazole linker and zinc as metal center. We report the formation of these coordination polymers using hydrothermal routes with water as solvent. These materials display one-dimensional structures with major structural modifications from minimal synthetic variations. What is more interesting, we have carried out antitumor measurements, and we have related these properties with the structural networks. To the best of our knowledge, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…A series of metal-organic chains (MOCs) based on 4-nitro-1 H -pyrazole as ligand and zinc as metal center has been reported and structurally characterized [ 212 ]. The antitumor properties of the 4-nitro-1 H -pyrazole ligand ( HL 40 ) and the MOCs complexes 40a ({[Zn 2 (μ-4-NO 2 -pz) 3 (μ-OH)]·H 2 O} n ), 40b ({[Zn 2 (μ-4-NO 2 -pz) 4 ]} n ) and 40c ({[Zn 3 (μ-4-NO 2 -pz) 4 (μ-ac) 2 (H 2 O) 2 ]} n ) ( Figure 21 ) were evaluated against three cancer cell lines (HT29, Hep-G2 and B16-F10).…”
Section: Miscellanea Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of metal-organic chains (MOCs) based on 4-nitro-1 H -pyrazole as ligand and zinc as metal center has been reported and structurally characterized [ 212 ]. The antitumor properties of the 4-nitro-1 H -pyrazole ligand ( HL 40 ) and the MOCs complexes 40a ({[Zn 2 (μ-4-NO 2 -pz) 3 (μ-OH)]·H 2 O} n ), 40b ({[Zn 2 (μ-4-NO 2 -pz) 4 ]} n ) and 40c ({[Zn 3 (μ-4-NO 2 -pz) 4 (μ-ac) 2 (H 2 O) 2 ]} n ) ( Figure 21 ) were evaluated against three cancer cell lines (HT29, Hep-G2 and B16-F10).…”
Section: Miscellanea Systemsmentioning
confidence: 99%
“…The s Table 1 D Zn-coordination complexes 40b and 40c showed a similar antitumor activity (average IC 50 48.23 and 45.13 μg/mL for 40b and 40c respectively), lower IC 50 than the free ligand (average IC 50 136.67 μg/mL), and with low specificity with respect to cell type ( Table 11 ). MOCs complexes 40b and 40c , prepared using water as solvent, can avoid the potential self-aggregation issue often encountered by some antitumor compounds such as triterpenes and minimize generic interactions, representing an alternative to traditional coordination complexes [ 212 ].…”
Section: Miscellanea Systemsmentioning
confidence: 99%
“…Traditionally, small organic molecules have been described with anti-cancer and anti-inflammatory properties useful as drugs [44,45]. Currently, has been reported that metal complexes possess remarkable advantages that render them as attractive alternatives to small organic molecules for the development of potential therapeutic agents, among others they show higher half-lives to allow their preferential tissue accumulation, due to their highest vascular permeability that permits their retention on tumor tissues [46].…”
Section: Raw 2647 Cell Viabilitymentioning
confidence: 99%
“…Metal complexes bearing triazole ligands are also considered one of the most biologically active materials. These complexes can be utilized in various agricultural and pharmaceutical applications because their activity can be easily tuned by varying metals, ancillary ligands, and coordination geometries. Particularly, zinc (Zn) complexes have been extensively investigated due to their chemical stability and physiological merits. Zinc ions exist in many chemical and biological systems as Zn 2+ species with a d 10 configuration, making them difficult to either oxidize or reduce. Since Zn 2+ ions can act as Lewis acids, they have a strong tendency to form stable adducts with triazole ligands.…”
Section: Introductionmentioning
confidence: 99%